Therapeutic Potential of Photosynthetic Microorganisms for Visceral Leishmaniasis: An Immunological Analysis - Vaitkevicius-Antão, Victor; Moreira-Silva, Jady; Reino, Isabelle Barreto da Silva Moreira; Melo, Maria Gabriella Nunes de; Silva-Júnior, José Noé da; Andrade, Alexsandra Frazão de; Araújo, Paulo Sérgio Ramos de; Bezerra, Raquel Pedrosa; Marques, Daniela de Araújo Viana; Ferreira, Silvana; Pessoa-e-Silva, Rômulo; Lorena, Virginia Maria Barros de; et al. (Frontiers in Immunology, 2022)
New therapeutic strategies have been studied to visceral leishmaniasis (VL) and for the development of an immunotherapeutic, new molecule that modulates the host’s immune response is necessary. The aim of this study was to evaluate in vitro, bioactive extracts of photosynthetic microorganisms (PMs) for its leishmanicidal/leishmanistatic and immunomodulatory potential. Bioactive extracts from PMs (Arthrospira platensis and Dunaliella tertiolecta) were obtained by sonication. Reference drugs, Miltefosine (MTF) and n-Methylglucamine Antimoniate (SbV), were also evaluated. The selectivity index (SI) of treatments was determined by assays of inhibitory concentration (IC50) in Leishmania infantum cells and cytotoxic concentrations (CC50), in human peripheral blood mononuclear cells by MTT method. The immune response was evaluated in healthy human cells by production of cytokines, nitric oxide (NO) and gene expression of Tbx21, GATA3, RORc and FOXP3, using four concentrations (CC50; ½ of CC50; ¼ of CC50 and IC50) to in vitro stimulation. Based on the data obtained, we observed that the extracts of the D. tertiolecta (SI = 4.7) and A. platensis (SI = 3.8) presented better results when compared to SbV (SI = 2.1). When analyzing the immune response results, we identified that the extracts of PMs stimulated the production of cytokines of the Th1 profile more than reference drugs. The extracts also demonstrated the ability to stimulate NO synthesis. Regarding gene expression, in all concentrations of A. platensis extract we found a balance between Th1 / Th2 profile, with the average expression of the Tbx21 gene more than GATA3 in the highest concentration (CC50). About the extract of D. tertiolecta, we can observe that in lowest concentrations a balance between all genes was present, with the average expression of the GATA3 gene being lower than the others. The best result, the ½ CC50 stimulating a balanced positive expression between the Th1xTh17xTreg profiles, with negative expression of GATA3. Thus, PMs extracts showed promising results, presenting low toxicity, leishmanicidal/leishmanistatic activity and induction of the immune response, which could be potential therapeutic candidates for VL.